Prevalence of Methicillin-Resistant Staphylococcus aureus using Molecular Biological Methods and its Antibiotic Resistance Patterns in Al-Ahsa Region of Saudi Arabia: Studies on MRSA isolates from Eastern Saudi Arabia - Iqbal, Zafar; Absar, Muhammad; Al-Sayel, Khowlah; Al-Mulhim, Munira; Al-Qahtani, Shouq; Al-Dawasari, Sarah; Al-Mulhim, Nourah; Fallatah, Nouf; Alomari, Maha; Adeel, Kanza; et al. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Methicillin-Resistant Staphylococcus aureus (MRSA) causes many clinical manifestations. In modern healthcare systems, the frequency of MRSA infections is used as the benchmark for the quality of healthcare. MRSAassociated clinical manifestations and antibiotic resistance differ in different regions of the world. No studies had previously been carried out on MRSA in Al-Ahsa Saudi Arabia. Therefore, we studied the prevalence and antibiotic resistance patterns of MRSA in our region. Overall, 2661 patients were tested for MRSA by employing GeneXpertbased PCR assay during Jan- Dec 2018, and data was analyzed using SPSS version 24. 146 patients were MRSA positive (5.48%), with a mean age of 45.17 years and a male to female ratio of 1:1.03. The highest frequency of MRSA was in the age group 60-79 years (25.43%) The prevalence of MRSA infection was highest between August to September (p-value < 0.001). Anemia, hypoalbuminemia, and leukocytosis were associated with MRSA infections (p < 0.001). 87.67% of patients had community-acquired infections (CA-MRSA) (p < 0.001). Prevalence of CAMRSA was the highest among the age group 60-70 years while the patient age group ≥ 80 years had the highest frequency of hospital-acquired infections (p = < 0.0003). Vancomycin and Linezolid showed 100% susceptibility, Penicillin, Cefoxitin, and Cefazoline 100% resistance while Oxacillin showed 98.9% resistance. The highest frequency of MRSA was found during scorching summer while the majority of the patients had CA-MRSA which necessitates precautions to be taken during top summer months. MRSA infections were significantly associated with anemia, hypoalbuminemia, and leukocytosis. Vancomycin and Linezolid could be drugs of choice for MRSA infections.